Testing of weak form efficiency on Bursa Malaysia’s selected industries / Muhammad Adib Akmal Noor Azlan - Noor Azlan, Muhammad Adib Akmal (Faculty of Business and Management, 2017)
The purpose of this study is to investigate the existence of Efficient Market Hypothesis (EMH) in Bursa Malaysia’s selected industries. However, this study is only testing the weak form of EMH. The industries chosen for this research is Construction, Consumer, Industrial and Tin and Mining industry. The data was collected in for each industry for daily, weekly and monthly basis from year 2011 to 2015. This study used Autoregressive Model to regress the past stock price with the current stock price. Tests employed for this study includes descriptive analysis, test for estimated empirical model, stationary tests and diagnostic tests. Result of this study reveals that for daily data, all of the industries has significant relationship which can be concluded as inefficiently weak. Meanwhile, for weekly data only consumer industry is inefficiently weak and for monthly data only industrial industry is inefficiently weak. All the other data for other industries can be concluded as efficiently weak. These results provide understanding towards investors, analysts and regulator in dealing with Efficient Market Hypotheses.